The Returns of Variable Moving Average Rules in China, Hong Kong, Singaporean and Malaysian Stock Markets - Ming-Ming, Lai; Siok-Hwa, Lau (2008)
This paper examines the profitability and predictability of index returns of Shanghai Composite Index, Hang Seng Index, Straits Times Index, and Kuala Lumpur Stock Exchange Composite Index over three sub-sample periods from 1(st) January 1996 to 30(th) September 2007. We used twelve variations of the variable moving average rules (VMA) that were adapted from Brock, Lakonishok, and LeBaron [5]. The results showed technical attractiveness and economic value significantly of VMA rules especially for the sub-period 2004 to 2007. Nonetheless, the profitability generated appears less consistent over time and the performance of VMA rules were more dominated by market trends movement. VMA rules generate more significant predictability for buy signals than sell signals. The interesting findings wan-ant future investigations.